Vi har inga konflikter, men... - en studie om hur personal inom äldreomsorg ser på konflikter, ansvarstagande och förebyggande insatser - Linde,Caroline (2010)
The purpose of this study was to examine how staff in the care of the elderly define conflicts, who they believe is responsible for resolving conflicts and how they look at conflict prevention. I have used a qualitative research method and interviewed six employees in a nursing home in the community care in the town of Helsingborg. I have analyzed my material through Granérs model which defines different types of conflicts. My results showed that the employees could not agree on a general definition of the meaning of conflicts, however they all felt that it was a sensitive subject. The results showed that the employee’s views on responsibility were relatively equal. The employees felt that there was a hierarchy, that some had more responsibility than others to resolve the conflict. They thought that it was primarily those involved in the conflict, next the group and finally the director’s responsibility to resolve the conflict. However, there were some members of the staff that thought the director has the overall responsibility. My results showed that the employees were generally positive to conflict prevention efforts, but it was not easy to describe how prevention should look. The employees, however, gave me many proposals for what could be conflict prevention efforts, such as: listen, inform, update, assist and provide, open communication, be honest, take responsibility, be open to development, taking things seriously, working after guidelines, comply with directives and workplace meetings. Keywords: conflict, conflict management, work environment, elderly care
Keywords: conflict management; work environment; elderly care; conflict; Konflikthantering; Arbetsmiljö; Äldreomsorg; Konflikt